Subclinical device-detected atrial fibrillation and stroke risk: a systematic review and meta-analysis. (10th January 2018) - Mahajan, Rajiv; Perera, Tharani; Elliott, Adrian D; Twomey, Darragh J; Kumar, Sharath; Munwar, Dian A; Khokhar, Kashif B; Thiyagarajah, Anand; Middeldorp, Melissa E; Nalliah, Chrishan J; Hendriks, Jeroen M L; Kalman, Jonathan M; et al.
Abstract: Aims: To determine stroke risk in subclinical atrial fibrillation (AF) and temporal association between subclinical AF and stroke. Methods and results: Pubmed/Embase was searched for studies reporting stroke in subclinical AF in patients with cardiac implantable electronic devices (CIEDs). After exclusions, 11 studies were analysed. Of these seven studies reported prevalence of subclinical AF, two studies reported association between subclinical and clinical AF, seven studies reported stroke risk in subclinical AF, and five studies reported temporal relationship between subclinical AF and stroke. Subclinical AF was noted after CIEDs implant in 35% [interquartile range (IQR) 34–42] of unselected patients with pacing indication over 1–2.5 years. The definition and cut-off duration (for stroke risk) of subclinical AF varied across studies. Subclinical AF was strongly associated with clinical AF (OR 5.7, 95% CI 4.0–8.0, P < 0.001, I 2 = 0%). The annual stroke rate in patients with subclinical AF > defined cut-off duration was 1.89/100 person-year (95% CI 1.02–3.52) with 2.4-fold (95% CI 1.8–3.3, P < 0.001, I 2 = 0%) increased risk of stroke as compared to patients with subclinical AF < cut-off duration (absolute risk was 0.93/100 person-year). Three studies provided mean CHADS2 score. In these studies, with mean CHADS2 score of 2.1 ± 0.1, subclinical AF was associated with annual stroke rate of 2.76/100 person-years (95% CI 1.46–5.23). After excluding patients without AF, only 17% strokes occurred in presence of ongoing AF. Subclinical AF was noted in 29% [IQR 8–57] within 30 days preceding stroke. Conclusion: Subclinical AF strongly predicts clinical AF and is associated with elevated absolute stroke risk albeit lower than risk described for clinical AF.